2019
DOI: 10.1002/alr.22403
|View full text |Cite
|
Sign up to set email alerts
|

Are rhinoviruses implicated in the pathogenesis of sinusitis and chronic rhinosinusitis exacerbations? A comprehensive review

Abstract: BackgroundRhinovirus (RV) infections are the most common cause of viral upper respiratory infections (URIs), and in the majority of persons they are self‐limiting. However, in others, viral URIs can progress to bacterial sinusitis and induce chronic rhinosinusitis (CRS) exacerbations.MethodsWe conducted a comprehensive Preferred Reporting Items for Systematic Reviews and Meta‐Analyses (PRISMA) review through April 2018 based on MEDLINE, EMBASE, Web of Science–Science Citation Index (SCI), and Conference Procee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 114 publications
0
14
0
Order By: Relevance
“…Among the epidemiologic studies which showed differential viral recovery in CRS vs control patients, 753,754,1006,1007 a consistent finding was that RV is either the most prevalent or one of the most prevalent viruses. A recent systematic review 1014 identified 5 studies that met a multi‐component quality review for potential bias. Three studies reported an association between RV and CRS, 1006,1015,1016 while 2 studies reported no association 1009,1010 .…”
Section: Chronic Rhinosinusitis Without Nasal Polyps (Crssnp)mentioning
confidence: 99%
“…Among the epidemiologic studies which showed differential viral recovery in CRS vs control patients, 753,754,1006,1007 a consistent finding was that RV is either the most prevalent or one of the most prevalent viruses. A recent systematic review 1014 identified 5 studies that met a multi‐component quality review for potential bias. Three studies reported an association between RV and CRS, 1006,1015,1016 while 2 studies reported no association 1009,1010 .…”
Section: Chronic Rhinosinusitis Without Nasal Polyps (Crssnp)mentioning
confidence: 99%
“…Chronic rhinosinusitis (CRS) is a heterogenous mucosal inflammation of the nasal cavity and paranasal sinuses ( 1 ). Although the pathophysiological causes of CRS remain unclear, accumulating evidence suggests that abnormal immune response of sinonasal mucosa to respiratory viral infection can progress to secondary bacterial infection and induce the exacerbation of CRS ( 2 6 ).…”
Section: Introductionmentioning
confidence: 99%
“…Rhinovirus (RV) infections are the most common cause of viral upper airway infections ( 4 , 7 , 8 ). However, it is unclear why they are self-limiting in the majority of persons, but in others can advance to bacterial sinusitis and enhance CRS exacerbations ( 2 6 ). A deeper understanding of host defense factors that contribute to effective protection against respiratory viral infection may aid in the prevention of disease progression and in the development of new therapeutic target.…”
Section: Introductionmentioning
confidence: 99%
“…A recent systematic review by Basharat et al showed that the prevalence of rhinovirus infections is increased in patients with CRS. Furthermore, rhinovirus infections incite inflammatory reactions that may result in CRS exacerbations and progression of disease (Basharat et al, 2019). Human bocavirus and metapneumovirus (hMPV) are also found in the nasal washes of CRS during flare-ups (Tan et al, 2017).…”
Section: Initiating Role Of the Virus In The Acute Crs Exacerbationmentioning
confidence: 99%